Regulating health and environmental risks under WTO law a critical analysis of the SPS agreement - Gruszczynski, Lukasz (Oxford : Oxford University Press, 2010)
The central problem that this book tackles is whether the system established by the SPS Agreement can address the existing and potential challenges of a new interdependent world. It provides a critical examination of the substantive provisions of the agreement and corresponding case law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Agreement on the Application of Sanitary and Phytosanitary Measures, -- (1995); Environmental law, International; Industrial hygiene -- Law and legislation; Commercial law; World Trade Organization